Static Magnetic Field Meter Using Rotating Search Coil Method - Rustamaji, Rustamaji; Sawitri, Kania (Emitor: Jurnal Teknik Elektro, 2024)
Abstract Static magnetic fields always exist the environment around us; besides being useful there are also negative impacts on humans, therefore it is necessary to have a tool to measure static magnetic fields. The purpose of this research is to produce a static magnetic field meter that can measure weak magnetic field. In this research, the design and realization of a static magnetic field meter using rotating search coil method is carried out, including: search coil, instrumentation and calibration amplifier, and display. Based on the results of measurements and tests that have been carried out, a static magnetic field meter with a coil area A = m2 and the number of turns N = 14 at a certain angular frequency (ω), can detect and measure a fairly small static magnetic field density (B) from various sources, for stable conditions: in the laboratory without any source of magnetic field can detect B = 2.127 to 2.375 mT, and with magnetic source (circular can detect B = 7.422 to 8.194 mT, neodymium can detect B = 11.03 to 11.84 mT, and smartphone X can detect B = 10.37 to 11.78 mT). Overall the device can work to detect and measure weak static magnetic fields with good measurement stability as seen from the relationship curve between supply voltage and the DC motor rotation which is linear, and measurement sensitivity up to B = 2.127 mT.